A Guide for Systems Engineers to Finding Your Role in 21st‐Century Software‐Dominant Organizations. Issue 1 (20th September 2021) - Sheard, Sarah; Bouyaud, Mickael; Osaisai, Macaulay; Siviy, Jeannine; Nidiffer, Kenneth E.
Abstract: The decision makers in many software‐dominant organizations, such as the FAANGs (Facebook, Apple, Amazon, Netflix, and Google), evolved quickly from coders and software engineers unfamiliar with the advantage of the big‐picture view of the software and of the organizations developing the software. INCOSE's Systems and Software Interface Working Group (SaSIWG) has been reading a fable of such an organization that found itself in a typical terrible state, unable to respond quickly and effectively to customer needs, because it was tied up in a complex mess of silos, dependencies, management rules, and blame. While the book has garnered praise as the answer to many software organizations' problems, it quite significantly omits any mention of systems engineering as well as much positive mention of architecture or project management. In response, the SaSIWG has been working on a set of tools to help first ourselves and then INCOSE systems engineers understand several important aspects of such organizations. First, how do such systems engineering‐deficient organizations work? Second, what does their terminology mean at a top level, in a way that doesn't take a computer science degree to understand or a day to look up? Third, how can a systems engineer break into the software engineering conversation and leave it without feeling defeated and overwhelmed by the unfamiliar jargon, but rather knowing they can be and have been useful? Finally, how can systems engineers plan in the long run to assist in engineering the complex system that is the software development enterprise and ecosystem? This is not always acknowledged as a system needing engineering, but it is universally acknowledged as "the problem" when it is not well engineered. This paper provides an overview of the tools that are being developed and outlines the guide that the group is hoping to create.